Utility of bedside lung ultrasound for assessment of lung recruitment in a case of acute respiratory distress syndrome - Abhijeet Singh; Ayush Gupta; Manas Kamal Sen; Jagdish Chander Suri; Shibdas Chakrabarti; Dipak Bhattacharya (Lung India, 2019)
Lung recruitment maneuvers are rescue measures commonly used to improve oxygenation in severely hypoxemic patients with acute respiratory distress syndrome (ARDS), who fail to improve on standard treatment. After recruitment, appropriate level of positive end-expiratory pressure (PEEP) is applied to prevent alveolar de-recruitment during expiration. Computed tomography scan of thorax and quasi-static pressure-volume curves have played a pivotal role are important in the assessment of recruitment, but they have several limitations. Lung ultrasound (LUS), which is now easily available in nearly every Intensive Care Unit, could be an attractive alternative method for assessing lung recruitment. It is noninvasive, easily repeatable and is devoid of radiation hazards. We are presenting a case of 24-year-old female patient with moderate ARDS in whom bedside LUS was successfully used into assessing lung recruitment as well as into determining the appropriate level of PEEP.